Konsumsi Kalsium dan Keluhan Menstruasi pada Remaja Putri di SMA Negeri 6 Tangerang - Oktabriawatie, Dyah; Mulyani, Erry Yudhya; Herlianti, Maria Poppy (Jurnal Nutrire Diaita (Ilmu Gizi), 2010)
AbstractCalcium is the mineral content of the most widely in the body, which is 1.5 to 2.0% of adult body weight or as much as ± 1 kg. The dietary requirement Calcium for adolescent girl is 1000 mg. The purpose of this study is to determine the relationship between Calcium consumption and menstruation disorders in adolescent girl aged 16-18 years at public high school 6, Tangerang. The data was collected on 7-9 May 2009. This study used simple random sampling, based on estimation formula, then the total subject is known to 81 girls. The data collected included: 1) Characteristics of sample: Height, Weight, Age, Nutritional Status; 2). Calcium Consumption was taken from recall 3x 24 hours with visual aids; 3) Menstruation Disorders was taken from questionnaire. The results shows that the average intake of Calcium adolescent girls (586.86mg ±385.478); Height (159.83cm ± 5.305); Weight (48.85kg±4.851); Age (16.16y±0.402); Nutritional status (1.80±0.401); 80.2% girls have menstruation disorders. There was a significant relationship between Calcium consumption and menstruation disorders in adolescent girls (p<0.05). There was no significant relationship between nutritional status, age and menstruation disorders (p>0.05). The average Calcium intake  in adolescent girls is still below the recommended adequacy rate, therefore it is necessary to encourage the adolescent girls to consume Calcium in an attempt to reduce mentruation disorders.Keywords: calcium consumption, menstruation disorders, adolescent girls Kalsium merupakan mineral yang paling banyak terdapat didalam tubuh, yaitu 1,5–2 % dari berat badan orang dewasa atau ± sebanyak 1 kg. Kebutuhan kalsium remaja putri adalah 1000 mg. Tujuan penelitian ini adalah mempelajari hubungan konsumsi kalsium, umur, status gizi remaja putri usia 16-18 tahun. Pengambilan data dilakukan pada tanggal 7-9 Mei 2009. Cara pengambilan sample dilakukan secara acak sederhana, berdasarkan rumus estimasi diketahui total subjek adalah 81 orang. Data yang dikumpulkan meliputi: 1) Karakteristik sample : TB, BB, umur, status gizi; 2) Konsumsi kalsium diambil melalui food recall 3x24 jam disertai alat bantu visual; 3) Keluhan menstruasi, di ambil melalui kuesioner keluhan-keluhan menstruasi. Hasil penelitian menunjukkan rata-rata konsumsi kalsium remaja putri 586,86 mg (±385,478); TB remaja putri 159,83 cm (± 5,305); BB remaja putri 48,85 kg (± 4,851); umur remaja putri 16,16 th (± 0,402); status gizi remaja putri 1,80 (± 0,401); keluhan menstruasi 80,2%. Ada hubungan yang signifikan antara keluhan menstruasi, dengan keluhan menstruasi pada remaja putri (p<0,05). Tidak ada hubungan yang signifikan antara status gizi dan umur dengan keluhan menstruasi (p>0,05). Konsumsi kalsium remaja putri masih dibawah anjuran perlu didorong untuk mengurangi keluhan mentruasi.Kata kunci: konsumsi kalsium, ketidak teraturan menstruasi, remaja putri